Raumnutzungskonflikt am Kvarner - Tourismus und Hafenexpansion - Büschenfeld, Herbert (ERDKUNDE, 1982)
The Adriatic coast of Yugoslavia has been undergoing a process of improvement for the last 25 years, which has been triggered and pushed forward by tourism on the one hand and by harbours and industry on the other. This process has progressed in the meantime to such an extent that the demands for space on the part of the initiators have been colliding ever more frequently. The resulting conflict situation is demonstrated by the example of the Kvarner Bay. First tourism in the Kvarner area is described: its genetic phases of development (winter holiday activities for the Austrian Hungarian upper class, conversion to warm weather coastal tourism, social tourism and package tourism), its present-day structure, its differentiation in space and its problems. Next the Kvarner port of Rijeka is dealt with by reference to its geographic position, especially in view of its transportation facilities, its rise to become the leading seaport of Yugoslavia caused by the advancing expansion of the hinterland, the corresponding extension of the harbour area, and above all by today’s development into the crude-oil terminal of the western Danube region and the petro chemical centre of Yugoslavia. The result of this dynamic development in the areas of both tourism and harbour expansion is a collision between their contra dietary demands on the use of space. In addition to the fact that tourism is beginning to be displaced by the expanding port area, this tourism is particularly affected by the intensive pollution of the Kvarner by a combination of hydro-carbons and sewage of high bacterial concentration, especially since the Kvarner represents an almost closed aquatic system whose renewal by oxygen-rich water from the Adriatic progresses only slowly.